Negative electrode and secondary battery
By adopting a negative electrode active material layer with a double-layer structure in the secondary battery, combining silicon and natural graphite materials, and controlling the difference in porosity and particle size, the uneven diffusion of lithium ions during the rapid charging process of secondary battery is solved. Problem, the fast charging and discharging performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202380048063.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-25
- Filing Date
- 2023-09-26
- Publication Date
- 2025-02-18
AI Technical Summary
The existing secondary batteries have poor performance during fast charging, resulting in uneven diffusion of lithium ions, which may lead to lithium precipitation and affect the battery's fast charging and discharge performance.
The negative electrode active material layer adopts a two-layer structure. The first and second layers contain silicon active materials and natural graphite respectively. By controlling the difference in porosity and optimizing the particle size of the natural graphite, the current density of the negative electrode is balanced and local Lithium precipitation.
By optimizing the structure of the negative electrode active material layer, the rapid charging and discharging performance of the secondary battery is significantly improved, preventing uneven diffusion of lithium ions and extending the service life of the battery.
Abstract
Description
[Technical field]
[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0125394 filed in the Korean Intellectual Property Office on September 30, 2022, and Korean Patent Application No. 10-2023-0128281 filed in the Korean Intellectual Property Office on September 25, 2023, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a negative electrode for a secondary battery and a secondary battery including the negative electrode. [Background Technology]
[0003] Secondary batteries are commonly used not only in portable devices but also in electric vehicles (EVs) and hybrid electric vehicles (HEVs) driven by an electric driving source.
[0004] Secondary batteries have attracted attention as a new energy source that improves environmental friendliness and energy efficiency due to their major advantages of being able to significantly reduce the use of fossil fuels and using energy without generating byproducts.
[0005] Generally, a secondary battery includes a positive electrode, a negative electrode, a separator and an electrolyte interposed between the positive electrode and the negative electrode, etc. In addition, electrodes such as the positive electrode and the negative electrode may be provided with an electrode active material layer on a current collector.
[0006] As the use of secondary batteries increases, a variety of battery performance is required. In order to improve battery performance, attempts have been made to add additives to the active material layer. Depending on the type of additive, some performance of the battery may be improved, but some performance may be deteriorated. Therefore, it is necessary to study the selection or combination of materials contained in the electrode that can improve the performance required for the secondary battery. [Summary of the invention]
[0007] [Technical issues]
[0008] The present invention is directed to providing a negative electrode for a secondary battery having improved rapid charging performance and a secondary battery including the negative electrode.
[0009] [Technical solution]
[0010] An exemplary embodiment of the present invention provides a negative electrode for a secondary battery, comprising: a collector; a first negative electrode active material layer disposed on the collector; and a second negative electrode active material layer disposed on the first negative electrode active material layer, wherein the first negative electrode active material layer and the second negative electrode active material layer contain a silicon-based active material and natural graphite, and the average particle size (D50) of the natural graphite is less than 9 μm, and the difference in porosity between the first negative electrode active material layer and the second negative electrode active material layer is less than 6%.
[0011] Another exemplary embodiment of the present invention provides a secondary battery including the negative electrode for a secondary battery according to the above exemplary embodiment, a positive electrode, and a separator.
[0012] [Beneficial Effects]
[0013] According to the exemplary embodiments described in this specification, in the negative electrode active material layer having a double-layer structure including a silicon-based active material and graphite, the fast charging performance can be maximized by controlling the porosity difference between the upper and lower layers and optimizing the particle size of the natural graphite. Specifically, the above-mentioned composition can prevent local lithium precipitation and improve the fast charge and discharge performance by balancing the current density of the negative electrode. If the difference in porosity between the upper and lower layers becomes larger, the lithium ion diffusion becomes uneven, and a phenomenon of local lithium ion enrichment occurs, which may lead to lithium precipitation. Small-particle natural graphite has a smaller particle size than large-particle natural graphite, so the diffusion distance of lithium within the particles is short, allowing rapid migration and charging. [Specific implementation method]
[0014] Hereinafter, the present invention will be described in more detail to better understand the present invention. The present invention can be implemented in various forms and is not limited to the exemplary embodiments described herein. The terms or words used throughout the specification and claims should not be interpreted as limited to their conventional meanings or dictionary meanings, but should be interpreted as having meanings and concepts consistent with the technical ideas of the present invention based on the principle that the inventor can appropriately define the concepts of the words or terms in order to best illustrate his invention.
[0015] It will be further understood that when used in this specification, the terms "comprises", "includes" or "has" specify the presence of stated features, numbers, steps, constituent elements and / or combinations thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, constituent elements and / or combinations thereof.
[0016] Furthermore, it will be understood that when an element such as a layer is referred to as being "on" another element, it can be "directly on" the other element, or intervening elements may be present. Conversely, when an element is referred to as being "directly on" another element, there are no intervening elements. Furthermore, when an element is referred to as being "on" a reference portion, the element is located above or below the reference portion, which does not necessarily mean that the element is located "above" or "on" in the opposite direction of gravity.
[0017] In this specification, the particle size refers to the average particle size expressed as D50. D50 can be defined as the particle size at 50% of the particle size distribution, which can be measured using a laser diffraction method. For example, a method for measuring the average particle size (D50) of a positive electrode active material may include dispersing particles of the positive electrode active material in a dispersion medium, introducing the dispersion into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), irradiating the dispersion with an ultrasonic wave of about 28 kHz with an output power of 60 W, and then calculating the average particle size (D50) corresponding to 50% of the cumulative volume in the measuring device.
[0018] In the present specification, description referring only to “active material layer” without the first and second expressions may be applicable to both the first and second active material layers.
[0019] A negative electrode for a secondary battery according to an exemplary embodiment of the present specification includes: a current collector; a first negative electrode active material layer disposed on the current collector; and a second negative electrode active material layer disposed on the first negative electrode active material layer, wherein the first negative electrode active material layer and the second negative electrode active material layer contain a silicon-based active material and natural graphite, and the average particle size (D50) of the natural graphite is 9 μm or less, and the porosity difference between the first negative electrode active material layer and the second negative electrode active material layer is 6% or less. In other words, the negative electrode for a secondary battery includes two layers of negative electrode active material layers, the porosity difference between the two layers of negative electrode active material layers is controlled to be below a specific value, and natural graphite with an average particle size (D50) controlled to be below 9 μm is used as an active material together with a silicon-based active material. With this configuration, the current density of the negative electrode can be balanced, and lithium precipitation at a local position can be prevented, thereby improving rapid charge and discharge performance.
[0020] According to an exemplary embodiment, the porosity difference between the first negative electrode active material layer and the second negative electrode active material layer may be 6% or less or 5% or less. In order to control such a porosity difference, the type of components contained in each layer, the particle size, the content of each component, the calendering conditions, etc. may be adjusted. For the calendering conditions, the calendering temperature, the calendering speed, the heating time of the calendering roller, etc. may be adjusted. For example, a method of heating the calendering roller before calendering to increase the roller temperature may be adopted. In this case, the temperature of the calendering roller may be controlled at a temperature of 30°C to 60°C. When the negative electrode active material layer of the double-layer structure is calendered using a heated calendering roller, the porosity difference between the upper and lower negative electrode active material layers may be reduced.
[0021] According to an exemplary embodiment, the porosity of the first negative electrode active material layer and the second negative electrode active material layer may be 1% to 40%, for example, 5% to 7%. If the porosity difference between the upper and lower layers is large, a difference in lithium ion concentration may occur, which may cause lithium ions to gather locally and cause lithium precipitation.
[0022] In this specification, the boundary between the first negative electrode active material layer and the second negative electrode active material layer can be confirmed by measuring the electrode cross section. For example, the boundary between the two layers can be confirmed by cutting the electrode cross section by ion milling and measuring the cross-sectional electrode with a scanning electron microscope.
[0023] According to an exemplary embodiment, the average particle size (D50) of natural graphite may be less than 9 μm, or 6 μm to 9 μm. The larger the particle size of natural graphite, the longer the diffusion distance of lithium within the particle, resulting in worse fast charging. On the contrary, the smaller the particle size, the shorter the lithium diffusion distance, the more conducive to improving fast charging. As an exemplary method for controlling the particle size of natural graphite, a method of reducing the large specific surface area by spheroidizing flaky natural graphite and treating the surface of the spheroidized natural graphite with a carbon coating can be used. Flaky natural graphite can be spheroidized by airflow classification. The carbon coating treatment of the surface can be performed by placing a precursor on a modified spherical natural graphite and then heat treating it. The precursor is used for carbon coating treatment on the surface of natural graphite, and as a non-limiting example, materials such as asphalt can be used.
[0024] According to an exemplary embodiment, the first and second negative electrode active material layers may further include artificial graphite. The average particle size (D50) of the artificial graphite may be 15 μm to 50 μm. When the average particle size (D50) of the artificial graphite is 15 μm or more, the negative electrode adhesion may be improved, and when it is 50 μm or less, the particle size may be effectively controlled, thereby improving the negative electrode fast charging performance.
[0025] According to one exemplary embodiment, the first and second negative electrode active material layers each may include 10 to 50 parts by weight, for example, 10 to 45 parts by weight of natural graphite, based on 100 parts by weight of the negative electrode active material.
[0026] According to an exemplary embodiment, the first and second negative electrode active material layers may each contain 50 to 99 parts by weight, 60 to 90 parts by weight, or 50 to 85 parts by weight of artificial graphite based on 100 parts by weight of the negative electrode active material. A higher content of artificial graphite than natural graphite may be beneficial for improving fast charging performance.
[0027] In an exemplary embodiment of the present specification, the silicon-based active material includes SiO x (0≤x<2),SiM y (M is a metal, 1≤y≤4) and at least one of Si / C. The silicon-based active material may include only one type, or may include two or more types together. When both negative electrode active material layers include silicon-based active materials, the two active material layers may use the same type of silicon-based active material, or different types or different combinations of silicon-based active materials.
[0028] In an exemplary embodiment of the present specification, the negative electrode active material layer containing a silicon-based active material may further contain a carbon-based active material. In this case, based on a total of 100 parts by weight of the active materials contained in the negative electrode active material layer containing the silicon-based active material, the content of the silicon-based active material may be 1 to 40 parts by weight, for example, 1 to 20 parts by weight.
[0029] The active material containing SiO x (0 ≤ x < 2) may be silicon-based composite particles containing SiO x (0 < x < 2) and pores.
[0030] SiO x (0 < x < 2) corresponds to the matrix in the silicon-based composite particles. SiO x (0 < x < 2) may be in the form of containing Si and SiO2, and Si may form a phase. That is, x corresponds to the ratio of the number of O to Si contained in SiO x (0 < x < 2). When the silicon-based composite particles contain SiO x (0 < x < 2), the discharge capacity of the secondary battery can be improved.
[0031] The silicon-based composite particles may further contain at least one of a Mg compound and a Li compound. The Mg compound and the Li compound may correspond to the matrix in the silicon-based composite particles.
[0032] The Mg compound and / or the Li compound may be present inside SiO x (0 < x < 2) and / or on the surface of SiO x (0 < x < 2). The initial efficiency of the battery can be improved by the Mg compound and / or the Li compound.
[0033] The Mg compound may contain at least one selected from the group consisting of Mg silicate, Mg silicide, and Mg oxide. The Mg silicate may include at least one of Mg2SiO4 and MgSiO3. The Mg silicide may include Mg2Si. The Mg oxide may include MgO.
[0034] In an exemplary embodiment of the present specification, based on a total of 100% by weight of the silicon-based active material, the content of the Mg element may be 0.1% by weight to 20% by weight, or 0.1% by weight to 10% by weight. Specifically, the content of the Mg element may be 0.5% by weight to 8% by weight, or 0.8% by weight to 4% by weight. When the above range is satisfied, the Mg compound can be contained in the silicon-based active material in an appropriate content, so that the volume change of the silicon-based active material during the charge and discharge process of the battery can be easily suppressed, and the discharge capacity and the initial efficiency of the battery can be improved.
[0035] The Li compound may include at least one selected from the group consisting of Li silicate, Li silicide, and Li oxide. The Li silicate may include at least one of Li2SiO3, Li4SiO4, and Li2Si2O5. The Li silicide may include Li7Si2. The Li oxide may include Li2O.
[0036] In an exemplary embodiment of the present invention, the Li compound may be in the form of lithium silicate. The lithium silicate is represented by Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and can be classified into crystalline lithium silicate and amorphous lithium silicate. The crystalline lithium silicate may exist in the silicon-based composite particles in the form of at least one lithium silicate selected from the group consisting of Li2SiO3, Li4SiO4, and Li2Si2O5, and the amorphous lithium silicate may be in the form of Li a Si b O c (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5). However, the present invention is not limited thereto.
[0037] In an exemplary embodiment of this specification, based on a total of 100% by weight of the silicon-based active material, the content of the Li element may be 0.1% to 20% by weight, or 0.1% to 10% by weight. Specifically, the content of the Li element may be 0.5% to 8% by weight, more specifically 0.5% to 4% by weight. When the above range is satisfied, the Li compound can be included in the silicon-based active material in an appropriate content, so that the volume change of the negative electrode active material during the charge and discharge process of the battery can be easily suppressed, and the discharge capacity and initial efficiency of the battery can be improved.
[0038] The content of the Mg element or the Li element can be confirmed by ICP analysis. For ICP analysis, after accurately taking a predetermined amount (about 0.01 g) of the negative electrode active material, it is transferred to a platinum crucible, and nitric acid, hydrofluoric acid, and sulfuric acid are added thereto, and it is completely decomposed on a hot plate. Then, by using an inductively coupled plasma atomic emission spectrometer (ICP-AES, Perkin-Elmer 7300), a reference calibration curve is obtained by measuring the intensity at the inherent wavelength of the Mg element or the Li element of the standard solution prepared using a standard solution (5 mg / kg). Subsequently, the pretreated sample solution and the blank sample are introduced into the spectrometer, the actual intensity is calculated by measuring the intensity of each component, the concentration of each component is calculated based on the obtained calibration curve, and then the calculation is converted so that the sum of the calculated concentrations of each component is equal to the theoretical value, and thus the content of the Mg element or the Li element in the prepared silicon-based active material can be analyzed.
[0039] In an exemplary embodiment of the present specification, the carbon layer may be disposed on the surface of the silicon-based composite particles and / or inside the pores. The carbon layer imparts conductivity to the silicon-based composite particles, thereby improving the initial efficiency, life characteristics, and battery capacity characteristics of a secondary battery including a negative electrode active material containing the silicon-based composite particles. Based on a total of 100% by weight of the silicon-based composite particles, the total amount of the carbon layer included may be 5% to 40% by weight.
[0040] In an exemplary embodiment of the present specification, the carbon layer may include at least one of amorphous carbon or crystalline carbon.
[0041] The average particle size (D50) of the silicon-based active material may be 2 μm to 15 μm, specifically 3 μm to 12 μm, and more specifically 4 μm to 10 μm. When the above range is met, the side reaction between the silicon-based composite particles and the electrolyte can be controlled, and the discharge capacity and initial efficiency of the battery can be effectively achieved.
[0042] In this specification, the average particle size (D50) may be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve of the particles. The average particle size (D50) may be measured using, for example, a laser diffraction method. In the laser diffraction method, particle sizes ranging from the submicron range to several millimeters can generally be measured, and results with high reproducibility and high resolution can be obtained.
[0043] The active material including Si / C as the silicon-based active material is a composite of Si and C, and is distinguished from silicon carbide represented by SiC. The silicon-carbon composite may be a composite of silicon, graphite, etc., and may form a structure in which a composite core of silicon, graphite, etc. is surrounded by graphene or amorphous carbon, etc. In the silicon-carbon composite, silicon may be nano-silicon.
[0044] In an exemplary embodiment of the present specification, the content of the negative electrode active material in 100 parts by weight of the negative electrode active material layer can be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and most preferably 98 parts by weight or more and 99.9 parts by weight or less.
[0045] According to one other exemplary embodiment of the present specification, the negative electrode active material layer may further include a negative electrode binder in addition to the silicon-based active material and the carbon-based active material.
[0046] The negative electrode binder can be used to improve the adhesion between the negative electrode active material particles and the adhesion between the negative electrode active material particles and the negative electrode collector. For the negative electrode binder, those known in the art can be used. Its non-limiting examples may include polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid and hydrogen are replaced by Li, Na or Ca etc. At least one of the above-mentioned materials in the group consisting of, and their various copolymers may also be included.
[0047] The content of the negative electrode binder may be 0.1 parts by weight to 20 parts by weight, for example, preferably 0.3 parts by weight to 20 parts by weight, more preferably 0.5 parts by weight to 10 parts by weight, based on 100 parts by weight of the negative electrode active material layer.
[0048] The negative electrode active material layer may not contain a conductive material, but if necessary, it may also contain a conductive material. The conductive material contained in the negative electrode active material layer is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; carbon fluorides; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; conductive materials, such as polyphenylene derivatives, etc. Based on 100 parts by weight of the negative electrode active material layer, the content of the conductive material in the negative electrode active material layer may be 0.01 parts by weight to 20 parts by weight, preferably 0.03 parts by weight to 18 parts by weight.
[0049] In an exemplary embodiment of the present specification, the thickness of each of the first and second negative electrode active material layers may be 5 μm or more and 500 μm or less. A thickness ratio of the first negative electrode active material layer to the second negative electrode active material layer may be 1:2 to 2:1.
[0050] In an exemplary embodiment of the present specification, the negative electrode collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, for the collector, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, aluminum or stainless steel each surface-treated with carbon, nickel, titanium or silver, etc. can be used. Specifically, transition metals such as copper and nickel that adsorb carbon well can be used for the collector. The thickness of the collector can be 1 μm to 500 μm. However, the thickness of the collector is not limited thereto.
[0051] One other exemplary embodiment of the present specification provides a secondary battery including the negative electrode of the above exemplary embodiment, a positive electrode, and a separator.
[0052] In an exemplary embodiment of the present specification, the positive electrode may include a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector and including a positive electrode active material. The thickness of the positive electrode active material layer may be 20 μm or more and 500 μm or less.
[0053] There is no particular limitation on the positive electrode collector, as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, aluminum or stainless steel with carbon, nickel, titanium or silver etc. treated on the surface, etc., can be used. In addition, the thickness of the positive electrode collector can generally be 1 μm to 500 μm, and the surface of the collector can be formed with fine concavoconvex to enhance the adhesion of the positive electrode active material. For example, the positive electrode collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams and non-woven fabrics.
[0054] In an exemplary embodiment of the present specification, the positive electrode may include a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) as an active material. The lithium composite transition metal compound may further include at least one of manganese and aluminum. The lithium composite transition metal compound may include 80 mol% or more, for example, 80 mol% or more and less than 100 mol% of nickel in a metal other than lithium.
[0055] In an exemplary embodiment, the content of the positive electrode active material in 100 parts by weight of the positive electrode active material layer may be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and most preferably 98 parts by weight or more and 99.9 parts by weight or less.
[0056] According to another exemplary embodiment of the present specification, the positive electrode active material layer of the above exemplary embodiment may further include a positive electrode binder and a conductive material.
[0057] The positive electrode binder can be used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material particles and the positive electrode collector. For the positive electrode binder, those known in the art can be used. Its non-limiting examples can include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, their various copolymers, etc., any one or a mixture of two or more thereof can be used.
[0058] The content of the positive electrode binder may be 0.1 parts by weight to 50 parts by weight, for example, preferably 0.3 parts by weight to 35 parts by weight, more preferably 0.5 parts by weight to 20 parts by weight, based on 100 parts by weight of the positive electrode active material layer.
[0059] The conductive material contained in the positive electrode active material layer is used to impart conductivity to the electrode, and can be used without particular limitation, as long as the conductive material has electronic conductivity without causing chemical changes in the battery. Specific examples may include: graphite, such as natural graphite and artificial graphite; carbon materials, such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, etc., any one of which or a mixture of two or more thereof can be used.
[0060] Specifically, in an exemplary embodiment, the conductive material may include one or more of single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT). Based on 100 parts by weight of the composition for the positive electrode active material layer, the content of the conductive material may be 0.1 parts by weight or more and 2 parts by weight or less, for example, preferably 0.3 parts by weight or more and 1.5 parts by weight or less, and more preferably 0.5 parts by weight or more and 1.2 parts by weight or less.
[0061] In addition to using the above-mentioned positive and negative active materials, the positive and negative electrodes can be manufactured according to the conventional methods for manufacturing positive and negative electrodes. Specifically, the active material layer-forming composition containing the above-mentioned active materials and optional binders and conductive materials can be applied to the collector, and then dried and rolled to manufacture the electrode. In this case, the types and contents of the positive and negative active materials, binders and conductive materials are as described above. The solvent can be a commonly used solvent in the art, such as dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone or water, and any one or a mixture of two or more thereof can be used. If the solvent can dissolve or disperse the active material, conductive material and binder in consideration of the coating thickness and manufacturing yield of the slurry, and then achieve a viscosity that can show excellent thickness uniformity when coating to manufacture the positive and negative electrodes, the amount of solvent is sufficient. Alternatively, the positive and negative electrodes can be manufactured by casting the active material layer-forming composition on another support, peeling off the film obtained from the support and stacking it on the collector.
[0062] The separator is used to separate the negative electrode from the positive electrode and provide a path for the movement of lithium ions, wherein any separator can be used as a separator without particular limitation, as long as it is commonly used in lithium secondary batteries, in particular, it is preferred to use a separator having high moisture retention capacity for the electrolyte and low resistance to the migration of electrolyte ions. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin polymer (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer), or a laminated structure of more than two layers thereof can be used. In addition, a common porous nonwoven fabric can be used, for example, a nonwoven fabric formed by high melting point glass fiber or polyethylene terephthalate fiber, etc. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator with a monolayer or multilayer structure can be selectively used.
[0063] Examples of the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten-type inorganic electrolyte that may be used in the manufacture of a lithium secondary battery, but are not limited thereto.
[0064] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.
[0065] As the non-aqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate or ethyl propionate can be used.
[0066] Particularly, in carbonate organic solvents, ethylene carbonate and propylene carbonate as cyclic carbonate are high viscosity organic solvents, because they have high dielectric constant, can dissociate lithium salts well, therefore can preferably use.When cyclic carbonate is mixed with the straight-chain carbonate (for example dimethyl carbonate and diethyl carbonate) with low viscosity and low dielectric constant with appropriate ratio, can prepare the electrolyte with high conductivity, therefore can more preferably use.
[0067] Lithium salts can be used as the metal salts. Lithium salts are materials that are easily soluble in non-aqueous electrolytes. For example, lithium salts selected from F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - 、PF6-、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N -One or more of the group consisting of is used as anion of the lithium salt.
[0068] In addition to the above-mentioned electrolyte components, the electrolyte may further contain one or more additives, such as halogenated alkylene carbonate compounds (such as difluoroethylene carbonate, etc.), pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, to improve the life characteristics of the battery, inhibit the reduction of the battery capacity, and improve the discharge capacity of the battery.
[0069] A secondary battery according to an exemplary embodiment of the present invention includes an assembly including a positive electrode, a negative electrode, a separator, and an electrolyte, and may be a lithium secondary battery.
[0070] Another exemplary embodiment of the present invention provides a battery module including the above-mentioned secondary battery as a unit cell and a battery pack including the battery module. Since the battery module and the battery pack include secondary batteries with high capacity, high rate capability and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large-sized equipment selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.
[0071] Since the secondary battery of the exemplary embodiment of the present invention stably exhibits excellent discharge capacity, output characteristics and cycle performance, the secondary battery can be used as a power source for the following devices: portable devices such as mobile phones, notebook computers and digital cameras, and medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems. For example, the battery module or battery pack can be used as a power source for any one or more of the following medium and large devices: power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles and plug-in hybrid electric vehicles (PHEVs); or power storage systems.
[0072] Example
[0073] Hereinafter, preferred embodiments will be provided to better understand the present invention. It will be apparent to those skilled in the art that these embodiments are provided only to illustrate the present invention, and various modifications and changes may be made within the scope and technical spirit of the present invention. Such modifications and changes are naturally within the scope of the appended claims herein.
[0074] Example 1
[0075] The first negative electrode active material layer is formed by coating a copper foil having a thickness of 15 μm with a first negative electrode active material layer-forming composition containing artificial graphite having a D50 of 20 μm, SiO, and natural graphite having a D50 of 9 μm as negative electrode active materials so that it has a thickness of about 33 μm in a dry state, and then drying it. The first negative electrode active material layer is formed by coating the first negative electrode active material layer with a second negative electrode active material layer-forming composition containing artificial graphite having a D50 of 20 μm, SiO, and natural graphite having a D50 of 9 μm as negative electrode active materials, and then drying it to form a second negative electrode active material layer, thereby preparing a negative electrode.
[0076] The first and second negative electrode active material layer forming compositions were prepared by mixing the above-mentioned negative electrode active material, Super C65 as a conductive material, styrene-butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener in a weight ratio of 96 (artificial graphite / natural graphite / SiO: 50 / 49 / 1): 1:2:1 (first negative electrode active material layer) and 96 (artificial graphite / natural graphite / SiO: 70 / 27 / 3): 1:2:1 (second negative electrode active material layer), and adding water, and each of the above compositions was coated on a copper foil.
[0077] After the composition is applied, the temperature of the calendaring roll is set before calendaring, and then the negative electrode is placed between the rolls and calendared. At this time, the temperature of the calendaring roll is set to about 40°C to 45°C.
[0078] The porosity difference between the prepared first and second negative electrode active material layers is 5%. The porosity difference is obtained by measuring the cross-sectional image of the negative electrode, dividing the upper and lower negative electrode active material layers, finding the pores while excluding the composition in each layer, calculating the porosity of each layer, and calculating the difference.
[0079] An electrolyte solution obtained by dissolving vinylene carbonate to 0.5 wt % and dissolving LiPF6 to a concentration of 1 M in a mixed solution of ethyl methyl carbonate (EMC) and ethylene carbonate (EC) mixed in a volume ratio of 7:3 was injected to prepare a lithium coin half-cell.
[0080] Example 2
[0081] The same procedure as in Example 1 was performed except that natural graphite having a D50 of 9 μm was used and the temperature of the calendering roll was 40° C. to 45° C. The difference in porosity between the prepared first and second negative electrode active material layers was 3%.
[0082] Comparative Example 1
[0083] The same procedure as in Example 1 was performed except that natural graphite having a D50 of 18 μm was used. The difference in porosity between the prepared first and second negative electrode active material layers was 5%.
[0084] Comparative Example 2
[0085] The same procedure as in Example 1 was performed except that the rolling was performed at a lower temperature (room temperature 25° C.). The difference in porosity between the prepared first and second negative electrode active material layers was 15%.
[0086] Comparative Example 3
[0087] The same procedure as in Example 2 was performed except that natural graphite having a D50 of 12 μm was used. The difference in porosity between the prepared first and second negative electrode active material layers was 7%.
[0088] Comparative Example 4
[0089] The same procedure as in Example 1 was performed except that natural graphite having a D50 of 10 μm was used. The difference in porosity between the prepared first and second negative electrode active material layers was 5%.
[0090] Comparative Example 5
[0091] The same procedure as in Example 1 was performed except that natural graphite having a D50 of 10 μm was used and the temperature of the calendering roll was about 30° C. The difference in porosity between the prepared first and second negative electrode active material layers was 10%.
[0092] The prepared half-cell was charged and discharged three times at 0.1C, and the discharge capacity of the third cycle was 1C, and it was charged in constant current (CC) mode (3C) for 15 minutes. In this process, the output voltage depending on the change of the state of charge (SOC) was differentiated to find the slope change point and determine the lithium plating SOC. In this way, the fast charging performance was evaluated.
[0093] [Table 1]
[0094] 3C lithium deposition SOC (%) Example 1 25 Example 2 29 Comparative Example 1 20 Comparative Example 2 20 Comparative Example 3 21 Comparative Example 4 22 Comparative Example 5 20
[0095] As shown in Table 1, the batteries prepared in Examples 1 and 2 show higher 3C lithium deposition SOC (%) values than Comparative Examples 1 to 5. The 3C lithium deposition SOC value is higher, and fast charging to a higher SOC can be achieved without lithium deposition. Therefore, it can be confirmed that Examples 1 and 2 have better half-cell fast charging performance than Comparative Examples 1 to 5.
Claims
1. A negative electrode for a secondary battery, comprising: Current collector; a first negative electrode active material layer disposed on the current collector; as well as a second negative electrode active material layer disposed on the first negative electrode active material layer; The first negative electrode active material layer and the second negative electrode active material layer contain a silicon-based active material and natural graphite, and the average particle size (D50) of the natural graphite is 9 μm or less, and The difference in porosity between the first negative electrode active material layer and the second negative electrode active material layer is less than 6%.
2. The negative electrode for a secondary battery according to claim 1, wherein The average particle size (D50) of the natural graphite is 6 μm to 9 μm.
3. The negative electrode for a secondary battery according to claim 1, wherein The first negative electrode active material layer and the second negative electrode active material layer further include artificial graphite.
4. The negative electrode for a secondary battery according to claim 3, wherein The average particle size (D50) of the artificial graphite is 15 μm to 50 μm.
5. The negative electrode for a secondary battery according to claim 1, wherein The first negative electrode active material layer and the second negative electrode active material layer each include 1 to 40 parts by weight of the silicon-based active material based on 100 parts by weight of the negative electrode active material.
6. The negative electrode for a secondary battery according to claim 1, wherein The first negative electrode active material layer and the second negative electrode active material layer each include 10 to 50 parts by weight of natural graphite based on 100 parts by weight of the negative electrode active material.
7. The negative electrode for a secondary battery according to claim 3, wherein: The first negative electrode active material layer and the second negative electrode active material layer each include 50 to 99 parts by weight of the artificial graphite based on 100 parts by weight of the negative electrode active material. 8 . A secondary battery comprising the negative electrode according to claim 1 , a positive electrode, and a separator.
9. The secondary battery according to claim 8, wherein: The positive electrode includes a lithium composite transition metal compound containing nickel (Ni) and cobalt (Co) as an active material.
10. The secondary battery according to claim 9, wherein The lithium composite transition metal compound further includes at least one of manganese and aluminum.
Citation Information
Patent Citations
Battery pack and device including the same
KR1020220125394A
Composition comprising a functional group bonded to a substrate and method for producing the same
KR1020230128281A